Role of Energy Metabolism in the Brown Fat Gene Program - Nam, Minwoo; Cooper, Marcus P. (Frontiers in Endocrinology, 2015)
In murine and human brown adipose tissue (BAT), mitochondria are powerful generators of heat that safely metabolize fat, a feature that has great promise in the fight against obesity and diabetes. Recent studies suggest that the action of mitochondria extend beyond their conventional role as generators of heat. There is mounting evidence that impaired mitochondrial respiratory capacity is accompanied by attenuated expression of Ucp1 and other BAT-selective genes, implying that mitochondria exert transcriptional control over the brown fat gene program. In this review, we discuss the current understanding of brown fat mitochondria, their potential role in transcriptional control of the brown fat gene program and potential strategies to treat obesity in humans by leveraging thermogenesis in brown adipocytes.